A arquitectura dos sentidos - um projecto de enoturismo no Douro - Bárbara Abreu Ventura Bernardo (2018)
The present dissertation starts from two key themes, essences for its elaboration: the architecture and the wine. This is intended to create a critical reflection on architecture as an experience for the senses, having as a framework Douro and wine production, basic data for the development of a winery. In addition to the disciplinary interest, the choice of this theme will allow the opportunity to study this industry, in constant evolution, as well as different architectonic attitudes with which it has been approached, with an intense conceptual and sensorial load. The analysis and definition of the different elements of Douro wine landscape, the understanding of the place, and the interpretation of the current framework of wine culture in architecture, will also allow us to perceive, albeit implicitly, the phenomenon of wine tourism as a vehicle for rapprochement between people and the cellars.All these elements will contribute to a better definition of a project strategy, and the construction of a program that can relate to the various spheres. The scope of rural tourism, which aims to requalify a vacant property space (promoting the integration of pre-existing spaces in a current program) and the scope of production tourism aimed at presenting a project for a contemporary winery. These will seek to be vehicles to combine the functional and perceptive aspects of architecture, technical and poetic aspects, as a proposal for the materialization of singular environments.